Contrast-enhanced ultrasound diagnosis of prostatic sarcoma: Two case reports - Wu, Guozhu (Medicine (Baltimore), 2021)
RATIONALE: Prostatic sarcoma (PS) is a very rare malignant tumor that accounts for <0.1% of prostate malignancies, and Ewing's sarcoma is an extremely rare form of PS. PATIENT CONCERNS: We reported on a 64-year-old patient with PS and a 36-year-old patient with Ewing's sarcoma, both of whom were examined by contrast-enhanced ultrasonography (CEUS) before surgery. DIAGNOSES: The 2 cases were proven to be prostatic stromal sarcoma, which was confirmed by imaging manifestations and histopathological findings. INTERVENTIONS: The 64-year-old patient underwent radical prostatectomy, and the 36-year-old patient underwent chemotherapy combined with local radiotherapy. OUTCOMES: PS showed diffuse enlargement of the prostate on sonography, and the necrotic liquefying area within the large vessels could be clearly displayed by CEUS. CEUS can be advocated as a valuable noninvasive and safe imaging diagnosis method for PS.